The effect of social-media communication on consumer perceptions of brands - Bruno Schivinski; Dariusz Dabrowski (Gdańsk University of Technology, Faculty of Management and Economics, 2013)
Researchers and brand managers have limited understanding of the effects of firm-created and user-generated social media communication on brand equity, brand attitude, and purchase intention. Thus, we investigated 504 Facebook users using a standardized online survey across Poland. To test the proposed model, we analyzed 60 brands across three different industries: non-alcoholic beverages, clothing, and mobile operators. In the data analysis, we applied the structural equation modeling technique. The results of our empirical studies showed that user-generated social media communication had a positive influence on brand equity and brand attitude. In addition, the analysis indicated that firm-created social media communication affected only brand attitude. Both brand equity and brand attitude showed a positive influence on purchase intention. Moreover, measurement invariance was assessed using a multi-group structural modeling equation. The findings revealed that the proposed model was invariant across the researched industries
Keywords: M31; M39; D83; 330; social-media; brand equity; brand attitude; purchase intention; Facebook